The need for long-term empirical studies in remote interpreting research: a case study of telephone interpreting - Ko, Leong (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Remote interpreting refers to the mode of interpreting in which the interpreter and clients do not meet in person and interpreting is conducted via media such as telephone or the Internet. Remote interpreting is becoming increasingly popular globally, particularly for community interpreting. However , this area is significantly under-researched and some of the findings of the limited existing research andfrom subjective observation do not accurately reflect the real situation. The findings of a long-term empirical study of sound-only telephone interpreting suggest that telephone interpreters can overcome the problems offatigue, stress, and a reduced concentration span after a period of interpreting practice and by using proper equipment. The paper concludes that long-term empirical studies are an essential methodology in remote interpreting research.